LASER HARDENING PROCESS ON Ck 45 DEPENDING ON THE LASER PARAMETERS - a small review - Vorkalis, Arturs; Lazov, Luybomir (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2023)
This study displays the effect of laser surface hardening parameters on the Ck 45 steel. The method is mostly based on experimental tests, with micro-hardness data being used to obtain the hardness profile Ck 45.The beauty of the surface laser hardening technique is that, it hardens a specific area without changing the surface qualities of the surrounding area. Due to its versatility and capacity to manufacture parts with complex geometry, laser heat treatment is regarded one of the best-performing manufacturing technologies currently in use.